Analisis Nilai Moral Perjuangan Ibu dan Anak dalam Film Mars: Kajian Sosiologi Sastra - Pitriani, Pipit; Alsunah, Aditya Ansor; Nurwahidah, Lina Siti; Julianto, Cecep Dudung (eScience Humanity Journal, 2025)
Literary works are a depiction of the imaginary life of a writer. One form of literary work is film. This study aims to describe the moral values ​​in the film entitled MARS "Mimpi Ananda Raih Semesta" by director Sahrul Gibran. This research was conducted using a descriptive qualitative method and a sociological approach to literature. The focus of this research is the moral values ​​contained in the film which is the object of research. To classify the data, moral values ​​according to Burhan Nurgiyantoro were used, which divide moral values ​​into three parts, namely (1) moral values ​​related to humans with themselves, (2) moral values ​​related to humans with other humans in the social and natural spheres, (3) moral values ​​related to humans with God. Data collection was carried out by document analysis through a review of scenes, dialogues, and the actions of the main characters. The results of this study indicate that in the film MARS "Mimpi Amanda Raih Semesta" there are three moral values ​​related to oneself in the form of hard work, never giving up, patience and determination, and self-confidence. Three moral values ​​related to others in the form of compassion, empathy, and mutual assistance. As well as two moral values ​​related to God in the form of sincerity and the power of prayer. This film depicts a mother who persistently fights for her child's education as a form of love, sacrifice and deep faith.